Parental relationship satisfaction in families of children with autism spectrum disorder (ASD): A multilevel analysis. Issue 7 (24th March 2017) - Langley, Emma; Totsika, Vasiliki; Hastings, Richard P.
Abstract : Caring for a child with Autism Spectrum Disorder (ASD) has been linked to a range of negative outcomes for parents but less is known about the putative impact upon the parental couple relationship. The relationship satisfaction of parents of children with ASD was investigated using multilevel modeling. Mothers and fathers (146 couples) reported on their relationship satisfaction, their own well‐being, and the behavior problems of the child with ASD and a sibling. Results indicated that mothers and fathers reported similar levels of relationship satisfaction and it was significantly and negatively associated with parental depression and the behavior problems of the child with ASD. Relationship satisfaction was unrelated to the behavior problems of a sibling, the number of children in the household, and family socioeconomic position (SEP). Further longitudinal research that captures a broader range of variables is required to build a theoretical understanding of relationship satisfaction in families of children with ASD. Current evidence suggests that early intervention routes targeting either child behavior problems, parental mental health, or the couple relationship have the potential to benefit inter‐connected subsystems within the broader family system. Autism Res 2017 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Autism Res 2017, 10: 1259–1268 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.